Effects of New Zealand blackcurrant extract on sport climbing performance - Potter, J. A.; Hodgson, C. I.; Broadhurst, M.; Howell, L.; Gilbert, J.; Willems, M. E.; Perkins, I. C. (European Journal of Applied Physiology, 2020)
Purpose: Blood flow to skeletal muscles and removal of metabolic by-products during a sport climb are essential to optimise performance and recovery. New Zealand blackcurrant (NZBC) extract has enhanced blood flow and performance in other exercise modalities. We examined the effect of NZBC extract on sport climbing performance and recovery. Methods: The study employed a double-blind, randomised, crossover design. Male sport climbers (n = 18, age 24 ± 6 years, height 179 ± 6 cm, mass 71.4 ± 7.8 kg, French grade 6a-8b) undertook 7 days supplementation of NZBC extract (600 mg/day CurraNZ™ containing 210 mg anthocyanins) or a placebo (PL). Climbing ability was assessed through hang time (HT), pull-ups and total climbing time (TCT) in 3 intermittent climbing bouts on a Treadwall M6 rotating climbing wall to exhaustion with 20 min recovery between climbs. Heart rate (HR), blood lactate (BL), forearm girth (FG) and hand grip strength (HGS) were recorded. Results: NZBC extract had no effect on pull-ups but provided a trend for higher HT and significantly improved TCT (+23%) compared to PL (-11%) over three climbs. HR, BL, FG and HGS all indicated that 20 min was insufficient for physiological recovery between the three climbing bouts indicating accumulative fatigue regardless of supplement condition. Conclusion: Despite indices of progressive fatigue across three bouts of climbing, NZBC extract facilitated not only a maintenance of TCT but an improved climbing endurance as compared with the PL condition. Blackcurrant anthocyanin-derived metabolites seem to affect physiological responses that facilitate sport climbing performance.